2018
DOI: 10.1080/03650340.2018.1552785
|View full text |Cite
|
Sign up to set email alerts
|

Suitable management options to improve the productivity of rice cultivars under salinity stress

Abstract: Growing rice in saline soils by minimizing damage on growth and yield remains a challenge. We conducted field experiments in the Africa Rice research field located in the Senegal River delta (16°11ʹ N, 16°15ʹ W) to study the effects of three management options of fertilization e.g. (i) nitrogen, phosphorus, and potassium fertilization: NPK; (ii) NPK combined with zinc: NPK-Zn, and (iii) NPK combined with gypsum: NPKgypsum on the soil salinity level, the nutrient uptake and the productivity of different rice cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…At the same time, an inverse trend was noted for K because maximum leaves K was accumulated by SRI-23 and minimum K was observed in the leaves of SRI-38. It has been reported that excessive sodium is metabolically toxic to plants and affects the survival and growth of rice plants which decreased grain yield and productive tillers (Mel et al, 2018). In the salinized environment, high uptake of K and low Na is positively correlated to salinity tolerance.…”
Section: Effect Of Salinity and Sodicity On Leaves Ionic Concentratio...mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, an inverse trend was noted for K because maximum leaves K was accumulated by SRI-23 and minimum K was observed in the leaves of SRI-38. It has been reported that excessive sodium is metabolically toxic to plants and affects the survival and growth of rice plants which decreased grain yield and productive tillers (Mel et al, 2018). In the salinized environment, high uptake of K and low Na is positively correlated to salinity tolerance.…”
Section: Effect Of Salinity and Sodicity On Leaves Ionic Concentratio...mentioning
confidence: 99%
“…In the salinized environment, high uptake of K and low Na is positively correlated to salinity tolerance. Preferential uptake of K over Na among the different genotypes is useful salinity tolerance criteria (Mel et al, 2018). K worked as a co-factor for more than 50 enzymes that may be susceptible to high Na (Munns and Tester, 2008).…”
Section: Effect Of Salinity and Sodicity On Leaves Ionic Concentratio...mentioning
confidence: 99%
“…One of the mechanisms of plant growth inhibition by salinity stress is an injury to cells caused by ion toxicity and nutritional imbalance. It is reported that excessive sodium (Na) uptake to the detriment of potassium (K) uptake may affect the growth and the survival of plants (Mel et al 2018); therefore; we focused on the ratio of the concentration of K to the concentration Na in plant leaf (leaf-K/Na) and attempted to explain relative yield as a function of this parameter.…”
Section: Introductionmentioning
confidence: 99%